Capital Contribution to the Business Value Creation - Ольга Михайловна Удовиченко; Ирина Владимировна Березинец; Евгения Валерьевна Сысолятина (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2010)
This article presents results dedicated to the development of indicators’ system enabling to evaluate intellectual capital (here and later – IC) contribution to the business value creation and the application of this system in the real company. In order to develop the model of evaluation of IC contribution to the value creation it is essential to analyze the main IC measurement systems, which are based on value-based management, then to identify value drivers and their interconnections with the basic categories of IC and to select indicators that allow to evaluate IC contribution to the company’s goals achievement, potential of its growth and development. Obtained valuations of indicators are presented by rating scales both for particular categories of IC and IC in a whole. As a result, the model which can be used as a guiding line for managers to analyze and overcome certain difficulties in increasing of IC contribution to the value creation in a company has been developed.